FATAL HEAD INJURY IN HOMICIDAL DEATHS IN BHOPAL REGION OF CENTRAL INDIA - DR. PRADEEP KUMAR MISHRA; DR. SANDEEP SINGH (International Journal of Pharma and Bio Sciences, 2012)
The head is a vital organ and the most vulnerable part of body to receive injuries. Injuries to the head are accidental, mostly vehicular or homicidal. Material and methods - The present study was based on retrospective analysis of 218 homicidal deaths in three years period from January 2004 to December 2006 from autopsies done in the Department of Forensic Medicine and Toxicology, Gandhi Medical College, Bhopal and Medico legal Institute, Home (Police) department, Government of Madhya Pradesh. The present study is carried out to assess the most vulnerable age group, sex incidence, seasonal variation, hospitalization, survival time, fatal period, defense wound and weapons used in order to get better perspective of the situation. Observation - The study was conducted on 218 alleged cases of homicide and the incidence of homicide by head injury was 39.7% (73 out of 218 homicides). There was predominance of male Conclusion - The present study has shown that victims in younger age groups, predominantly males, are vulnerable to homicidal head injuries. Head injuries were predominantly caused by blunt weapon. In the majority of cases injuries were severe in nature, involving all the structures of the head (scalp, skull, brain and/or meninges). Most of the cases died on the spot, before health facilities could be provided, as brain is a vital organ and injury over this organ is likely to cause death.